1994
DOI: 10.1039/ja9940900045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of discharge conditions on the sputtering and spatial distribution of atoms in a radiofrequency glow discharge atomizer for atomic absorption spectrometry

Abstract: The effects of discharge conditions on the sputtering, spatial distributions and transport patterns of sputtered atoms in a demountable, radiofrequency (r.f.) glow discharge (GD) atomizer, were investigated. Results obtained for sputtering of oxygen-free hard copper indicate that the GD plume is constricted by an increase in the Ar gas pressure and disturbed by Ar gashacuum flow. It is shown that the glow is an inhomogeneous medium and that most of the sputtered Cu atoms are localized in the front of the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Several studies have been carried out by Marcus and coworkers to investigate the role of discharge conditions and the optimum design of the chamber in rf-GD coupled to AAS (able to measure free gas-phase atoms) [73,74,75,76]. Their results indicated that large anode diameters give rise to higher absorbance.…”
Section: Radiofrequency Glow Discharge-atomic Absorption Spectrometrymentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have been carried out by Marcus and coworkers to investigate the role of discharge conditions and the optimum design of the chamber in rf-GD coupled to AAS (able to measure free gas-phase atoms) [73,74,75,76]. Their results indicated that large anode diameters give rise to higher absorbance.…”
Section: Radiofrequency Glow Discharge-atomic Absorption Spectrometrymentioning
confidence: 96%
“…Spatial distributions and transport patterns of sputtered atoms have also been studied [74]. Further studies examined the effect of anode dimensions and location of the discharge gas inlet port on the spatial distribution of Cu atoms in rf-GD-AAS [76].…”
Section: Radiofrequency Glow Discharge-atomic Absorption Spectrometrymentioning
confidence: 99%
“…Similar measurements, but with a diode laser as primary source, were carried out by Uzelac and Leis, 86 for the argon metastable atoms in a microwave boosted Grimm source. Moreover, Hoppstock and Harrison 87 and Absalan et al 88 monitored two-dimensional spatial distributions of sputtered atoms in a dc and an rf glow discharge, respectively, but only relative profiles (i.e., absorbance data) were obtained. Finally, Larkins 89 investigated the effect of traces of water vapour on the amount of absorption by sputtered atoms.…”
Section: Atomic Absorption Spectrometrymentioning
confidence: 99%
“…Absorbance signals increased with the size of the limiting orifice diameter and with discharge power, but at higher power there was a compromise between ablation rate and source stability. Absalan et al (336) concluded that the rf source sustained a plasma stable enough for sequential AAS and depth profiling of metal samples. Inhomogeneity of the glow discharge was noted, and independent control of flow rate and pressure of the sputtering gas was critical for controlling the spatial distribution of atoms.…”
Section: Other Techniquesmentioning
confidence: 99%